Mapping Quality Gaps of Islamic and Non-Islamic Kindergarten: A Systematic Literature Review - Prihantoro, Agung; Ndayizeye, Oscar; Atymtaevna, Begimbetova Guldana (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
Quality of Islamic and Non-Islamic kindergarten is a serious problem to solve immediately. But no research is done on mapping quality gaps of kindergarten in the world. This research mapped quality gaps of kindergarten in the whole world. Research method is systematic literature review. Results of the research reveals that quality gaps of kindergarten were mapped into seven categories. They are (1) learning opportunity, (2) accreditation instrument, (3) graduate competence, (4) learning process, (5) teacher and education personnel, (6) facilities, (7) parent involvement. There is no different categories among Islamic and non-Islamic kindergartens. These gaps spread around the world in America, Asia and Europe continents. No article presents the gaps in Africa and Australia continents and it bears little big questions.